2012
DOI: 10.1111/j.1365-2842.2012.02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal diseases and stress: a brief review

Abstract: Periodontal diseases are common chronic inflammatory diseases caused by pathogenic microorganisms colonising the subgingival area and inducing local and systemic elevations of pro-inflammatory cytokines resulting in tissue destruction. Apparition and evolution of periodontal diseases are influenced by many local or systemic risk factors. Psychological stress has been suggested as one of them and may negatively influence the outcome of periodontal treatment. However, mechanisms explaining the possible relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 90 publications
(115 reference statements)
2
72
2
3
Order By: Relevance
“…From there, studies conducted on animals [19][20][21] and on people, whether it be cohort, cross-sectional, case-control or clinical trials [6,15,28,22] showed a positive correlation between stress and the occurrence of periodontal disease. According to several recent literature reviews, the evidence is currently sufficient to suggest that stress is a risk factor for the occurrence of periodontal disease in the presence of pathogens as well as the worsening of pre-existing periodontal diseases [8,12,15,17,[23][24][25][26].…”
Section: Progressive Establishment Of the Link Between Chronic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…From there, studies conducted on animals [19][20][21] and on people, whether it be cohort, cross-sectional, case-control or clinical trials [6,15,28,22] showed a positive correlation between stress and the occurrence of periodontal disease. According to several recent literature reviews, the evidence is currently sufficient to suggest that stress is a risk factor for the occurrence of periodontal disease in the presence of pathogens as well as the worsening of pre-existing periodontal diseases [8,12,15,17,[23][24][25][26].…”
Section: Progressive Establishment Of the Link Between Chronic Stressmentioning
confidence: 99%
“…Overconsumption of high-fat foods induced by stress can lead to increased cortisol production and thus immunosuppression [35,37]. Any changes to diet can cause stress and can be a risk factor for periodontal disease [25,35].…”
Section: Changes To Dietmentioning
confidence: 99%
“…There are several main causal risk factors, (i) the subgingival bacterial biofilm on both the tooth root surface and on the pocket epithelial lining (12), (ii) genetic risk factors and epigenetic modifications (9,13,14), (iii) life style related risk factors, such as smoking, stress and poor diet or micronutrients intake (15)(16)(17), (iv) systemic disease, notably diabetes (18) and (v) others factors as of yet unknown, but possibly occlusal disturbances or fremitus, iatrogenic aspects (19) (Figure 1). …”
Section: Periodontitis Is a Complex Diseasementioning
confidence: 99%
“…Elevation of salivary alpha-amylase activity correlated with elevation of the CPI value, but not the OHI value. Periodontal disease is reported to relate to physical and emotional stress 37) . The results of our study suggest that stress could have made the periodontal condition worse in a stressed participant, even if their oral hygiene was good.…”
Section: Discussionmentioning
confidence: 99%